(3TQM eSGFd Mfjf Hf GSMGbs - (3CHh GdbGSe , YHO GdQMef Hf Ydj Hf CHi UGOb GdfjSCHhQis; (3GHf CHj UGOb , YHO GdQMef Hf Ydj Hf CMeO Hf CHj UGOb, CHh GdbGSe (B- (3HbQGW GdKGfj GdfjSCHhQj,J (B470 (3g` ? s ((3jhSa Hf GdbS efUhQ GdShjOi , GdJWHH s)
(3ChdgG (B:s
(3JHOC Hbhdg GdYde HGdCeQGV , hEdi GdYde HGdCSHGH hEdi GdYde HGdOdGFd s
(3BNQgG (B:s
(3GdHhd hGdLhY hcPdc GdMQcGJ GdTOjOI hGdZVH hef gGgfG adfNJe GdcJGH s
(3fSNI CNQi JfbU (B16 (3hQbI ef ChdgGs
(3GdfGSN cJHgG dfaSgs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdWHs